Amores, vapores e dinheiro- masculinidades, homossexualidades nas saunas de michê em São Paulo - Santos, Elcio Nogueira dos (2012)
This text questions the hegemonic masculinities concept and subordinate variants of these masculinities. It has as a hypothesis that hegemonic masculinities and their subordinate variants depend of the historical time and the culture they are inserted in. In other words, there is not a universal and ahistorical model of hegemonic masculinity. It takes as analysis focus the relations established between a group of men who buy sex from sex workers and the sellers, here denominated boys, male prostitutes and sex workers, in enclosed spaces, or male prostitutes bathhouses in the city of São Paulo, places which offer the service of these professionals. It was used as method of research participant observation and semi-structured and in depth interviews with sex workers and their clients. It became possible through the study of this group of men to discuss that hegemonic masculinities and their subordinate variants are in frequent contest for the power and hegemony of the groups, whether it is the group of the clients, whether it is the group of sex workers. It also questioned this group s desire, affection and its intergenerational relations. It proposes that the relations between sex workers and clients are originated from the partners desire and, in some relations, deepen, then constituting new affectivities between the same partners. It brings to discussion the social markers of difference that exist in male prostitutes bathhouses and that configure hegemonies and subordinate between masculinities. It also discusses the relations of power between these groups